Pemanfaatan Radioisotop dalam Diagnosis Medis: Tinjauan Fisika Inti terhadap Akurasi dan Efektivitas Diagnostik Medis - Sri Wahyuni; Miftahul Jannah (Physics Department, Faculty of Mathematics and Natural Sciences, Universitas Negeri Makassar, 2026)
Nuclear physics has contributed significantly to modern medicine, particularly through the use of radioisotopes in medical diagnosis. Radioisotopes such as Tc-99m, F-18, I-131, and Ga-68 are widely applied in imaging modalities including Single Photon Emission Computed Tomography (SPECT) and Positron Emission Tomography (PET), enabling non-invasive visualization of physiological processes at the molecular level. This literature review examines the physical principles underlying radioisotope production and decay, their pharmacokinetics in the human body, as well as the accuracy and clinical effectiveness of radioisotope-based diagnostic techniques. Analysis of 17 selected journal articles indicates that PET imaging using F-18-FDG achieves diagnostic sensitivity and specificity exceeding 90% for oncological applications, while Tc-99m SPECT demonstrates high reliability for cardiac and neurological assessments. However, key challenges remain including radiation exposure management, cost of cyclotron-produced radioisotopes, and limited generator availability in developing countries. The review concludes that continued advances in detector technology, radiopharmaceutical design, and image reconstruction algorithms are critical to improving the diagnostic accuracy and expanding access to nuclear medicine.